Demand and Supply of Fuelwood and Timber in India - Rai, S. N.; Chakrabarti, S. K. (Indian Forester, 2001)
The aggregate demand for the year 1996 of fuelwood for the country was 201 million tonnes i.e. 213.8 kg per capita, per year for a population of 940 million. Similarly the demand of timber was 92 million m3 i.e. 0.098 m3 or 3.5 cft per capita per year. The current sustainable production of fuel wood from forests is 17 million tonnes and from farm forestry and other areas 98 million tonnes. There is net deficit of 86 million tonnes of fuel wood, which as a compulsion is being removed from the forests. The situation regarding timber (at current productivity) is not grave but moratorium on fellings and market demands creates pressure. The paradox is that forests produce 70 per cent timber and 30 per cent fuel wood, while the demand for wood is around 70 per cent as fuel wood and 30 per cent as timber. This really exacerbates the situation. The forests have at least 5 times more pressure on them for fuel wood and small timber than what they can withstand, as a matter of sustained productivity.